From Retribution to Restoration - Arunesh Babu; Shanthi Simon (Acta Neophilologica)
Retributive justice, which is rooted in feudal, colonial, and punitive structures, has enabled systemic inequalities, putting the marginalised and disadvantaged at the most risk. These frameworks, established through absolutist bureaucracies, continued in a postcolonial setting, obstructing the reintegration of criminals into society. Victor Hugo critiques these unfair power structures from an abolitionist perspective in his book Les Misérables (1862). By examining Jean Valjean's transformation from a hardened criminal to a compassionate individual, inspired by Bishop Myriel’s act of mercy, the paper emphasises how restorative justice can facilitate personal growth and societal restoration. This paper critiques colonial justice for its emphasis on punishment and its role in reinforcing socio-economic imbalances. It also discusses alternative justice methods that prioritise reconciliation and reintegration, demonstrating how these approaches tackle the underlying causes of crime while fostering equity and community building. Through Hugo’s narratives and its connections to postcolonial realities, the paper highlights the necessity of transitioning from punitive to restorative models that dismantle systemic inequalities and promote collective responsibility.